Big Panda and tiny Dragon - Norbury, James (Michael Joseph (Penguin Books), 2021)
Discover the most beautiful book of the year as seen on ITV News and in the Guardian THE SUNDAY TIMES BESTSELLER 'James has a way to speak to your soul. This book is nothing short of comforting and heart warming' VEX KING' While the drawings have the charm of Winnie-the-Pooh, the captions have the depth of ancient proverbs' GUARDIAN'A beautifully illustrated book which draws on tender moments. Exquisite' DR RANGAN CHATTERJEE________A guiding light in the darker months, Big Panda and Tiny Dragon is the beautifully illustrated and mindful journey of two friends through the seasons, inspired by Buddhist philosophy'Which is more important,' asked Big Panda, 'the journey or the destination?''The company,' said Tiny Dragon.Friends Big Panda and Tiny Dragon journey through the seasons of the year together, day and night, in rain and in sun. Travelling through nature, they find hope and inspiration in the world around them, realising that even in the darkest of days, Spring will always return. Feel the calming influence of Big Panda, who reminds us of the bigger picture while appreciating the simplicity of small moments. Explore your surroundings with the inquisitive eye of Tiny Dragon, our friend who is big in heart if not in stature.And on their journey through the ever-changing seasons, join these two friends as they learn how to live in the moment, be at peace with uncertainty, and find the strength to overcome life's obstacles, by Buddhist philosophy and spirituality, the story of these whimsical characters makes the perfect gift for anyone looking for a little hope and comfort. The two friends often find themselves lost but discover beautiful sights they never would have found if they had gone the right way. While the drawings have the charm of Winnie-the-Pooh, the captions have the depth of ancient proverbs' GUARDIAN
Keywords: Children Story- Pictorial Book; Children Story- Seasons wise